Preliminary study of water quality based on the physico-chemical assessment on three selected rivers in Bandar Tun Abdul Razak Jengka / Aisyah Aqilah Aziz ... [et al.] - Aziz, Aisyah Aqilah; Md Isa, Nurun Nadhirah; Nawi, Liliwirianis; Shaikh Nasir, Nur Thabitah (Universiti Teknologi MARA Cawangan Pahang, 2021)
The increasing demand for clean water consumption corresponds with the rapid development of population and urbanization. An increasing amount of human wastes, which predominantly come from domestic and industrial wastes, is finally discharged into the water body. Thus, this study was done to identify the water quality based on physico-chemical assessments which are pH, dissolved oxygen, temperature, and turbidity from three selected rivers namely the Jengka River, the Chenerai River, and the Jempul River which are located within Bandar Tun Abdul Razak, Jengka. Water samplings were done by taking a continuous physico-chemical parameter of the three rivers for eight weeks. The results of the study were compared to the National Water Quality Standard for Malaysia (NWQS) which was introduced by the Department of Environment (DOE) Malaysia. The findings showed that all four selected parameters were under optimum value after comparing with the allowable limit by the NWQS. Therefore, the three rivers in Bandar Tun Abdul Razak, Jengka are still safe and clean for daily use.